Substitusi Tepung Ikan Dan Tepung Bungkil Kedelai Dengan Tepung Daun Indigofera (Indigofera zollingeriana) Dalam Ransum Terhadap Kualitas Fisik Dan Kandungan Protein Daging Ayam Broiler - Tandang Gumelar, Gilang; Somanjaya, Rachmat; Imanudin, Oki (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2025)
This study aims to analyse the physical quality and protein content of broiler chicken meat resulting from the substitution of fish meal and soybean meal with Indigofera (Indigofera zollingeriana) leaf meal (ILM) in the ration and to obtain the ideal substitution level of fish meal and soybean meal with Indigofera leaf meal in the ration to produce the best physical quality and protein content of broiler chicken meat. The study was conducted experimentally on 100 broiler chickens for 35 days using a Completely Randomized Design (CRD). The treatments given were the substitution of fish meal and soybean meal in the ration with five levels of ILM, namely: 0% (P0 as control), 25% (P1), 30% (P2), 35% (P3), and 40% (P4), each treatment was repeated 4 times. The variables observed included the degree of acidity (pH), cooking loss, water-holding capacity (WHC), and meat protein content. The data obtained were analyzed using variance analysis (ANOVA) and further tested using Duncan's Multiple Range Test (DMRT). The results showed that substituting fish meal and soybean meal in the ration did not significantly affect (p>0.05) the pH value and cooking loss of broiler chicken meat. In contrast to the variable of water holding capacity, the ILM substitution of 25% produced the highest number (p<0.05) compared to the control and other substitution levels, which was 37.38%. The lowest meat water holding capacity occurred at % ILM substitution level of 40% (19.64%). Furthermore, the crude protein content of the meat showed an increasing trend along with the ILM substitution level. The highest crude protein content was obtained at the ILM substitution level of 35%, significantly different (p<0.05) from the control treatment and the ILM substitution level of 25%. Substituting fish and soybean meal with ILM increased the crude protein content and physical properties except for broiler chicken meat's pH and cooking loss value.